2019
DOI: 10.1002/ajmg.a.61281
|View full text |Cite
|
Sign up to set email alerts
|

Expanding phenotype with severe midline brain anomalies and missense variant supports a causal role for FOXA2 in 20p11.2 deletion syndrome

Abstract: Rare individuals with 20p11.2 proximal deletions have been previously reported, with a variable phenotype that includes heterotaxy, biliary atresia, midline brain defects associated with panhypopituitarism, intellectual disability, scoliosis, and seizures. Deletions have ranged in size from 277 kb to 11.96 Mb. We describe a newborn with a de novo 2.7 Mb deletion of 20p11.22p11.21 that partially overlaps previously reported deletions and encompasses FOXA2. Her clinical findings further expand the 20p11.2 deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…This potential time dependent crosstalk may be mediated through the downstream targets of Notch and Tgfβ signals, since it is shown that both signals can regulate similar target genes (Klüppel & Wrana 2005;De Jong et al 2004), including foxa2, a member of the FOX family of transcription factors (both signals suppress foxa2 expression) (Kondratyeva et al 2016;Liu et al 2012). In our study, we found upregulation of foxa2 in the flapped snout region, and interestingly, a recent study in human shows that a deletion in Foxa2 can cause specific facial deformities including a shallow nasal bridge, a short upturned nose, and a downturned nasolabial fold (Dines et al 2019). In addition, we found rbpjb, a major transcription factor mediating canonical Notch signal in various cell types (Tanigaki et al 2002) to be differentially expressed in the flapped snout of both species.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This potential time dependent crosstalk may be mediated through the downstream targets of Notch and Tgfβ signals, since it is shown that both signals can regulate similar target genes (Klüppel & Wrana 2005;De Jong et al 2004), including foxa2, a member of the FOX family of transcription factors (both signals suppress foxa2 expression) (Kondratyeva et al 2016;Liu et al 2012). In our study, we found upregulation of foxa2 in the flapped snout region, and interestingly, a recent study in human shows that a deletion in Foxa2 can cause specific facial deformities including a shallow nasal bridge, a short upturned nose, and a downturned nasolabial fold (Dines et al 2019). In addition, we found rbpjb, a major transcription factor mediating canonical Notch signal in various cell types (Tanigaki et al 2002) to be differentially expressed in the flapped snout of both species.…”
Section: Discussionsupporting
confidence: 75%
“…It is, therefore, possible that the two other FOX members identified by RNA-seq and qPCR, foxf1 and foxa2, are the key regulators of the entire list of DEGs, since they might bind to the consensus FOX binding site. In addition, both foxf1 and foxa2 displayed consistently increased expression in the flapped snout in both comparisons, and are also implicated in the nose morphogenesis in mammals (Dines et al 2019;Kucharczyk et al 2014). We have recently found foxf1 among the regulators of lip hypertrophy in an East African cichlid species as well (Lecaudey et al 2021), suggesting a potentially important and general role of foxf1 in soft tissues exaggeration in cichlids, and given the potential role of foxd3 and foxp1 in cichlid fin exaggeration, FOX genes may play a more general role in tissue elaboration in vertebrates.…”
Section: Discussionmentioning
confidence: 92%
“…During pancreatic development, FOXA2 is expressed at early stages starting from the endoderm stage and its protein level is increased during the endocrine specification stage 1,9 , while the exocrine and ductal cells express a low level of FOXA2 9 . Mouse studies showed that Foxa2 is important for islet development and beta-cell functionality 6,[10][11][12] and its specific deletion in beta-cells leads to hyperinsulinemic hypoglycemic phenotype 13,14 . In human, previous reports demonstrated that patients with heterozygous FOXA2 mutations develop hyperinsulinemia, hypoglycemia, hypopituitarism, endodermal organ defects, and craniofacial abnormalities 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…We compared our case with those reported to have deletions of chromosome 20p11.2, including FOXA2 ( 2 , 5 , 6 , 7 , 12 , 13 , 14 ). All cases except one reported hypopituitarism.…”
Section: Discussionmentioning
confidence: 99%
“…All cases except one reported hypopituitarism. However, only a few reports have described hyperinsulinemic hypoglycemia in detail, whereas several reports have described clinical findings suggestive of hyperinsulinemic hypoglycemia ( 13 , 14 ). It has been reported that many cases of epilepsy are associated with 20p11.2 deletions, but our patient did not develop epilepsy.…”
Section: Discussionmentioning
confidence: 99%